Parastomal Gallbladder Herniation as an Incidental Preoperative Computed Tomography Finding - Smarda, Magdalini (Case Rep Radiol, 2021)
A 65-year-old woman with a long surgical history was referred to our hospital's Colorectal Unit for ileostomy management. The patient retained an ileostomy for almost a decade after a series of complicated operations she had undergone, which had several side effects such as electrolyte imbalances, high output, weight loss, and a parastomal hernia. Our hospital's colorectal surgeon proposed to replace the ileostomy with a permanent sigmoidostomy and asked for an imaging evaluation of the parastomal hernia content before the surgery. A computed tomography of the abdomen was performed using our Computed Tomography Department's 64-detector row CT scanner after oral administration of contrast media, without intravenous contrast media injection due to allergy. Concerning the parastomal ileostomal hernia, besides small bowel loops with intraluminal gastrografin, inside the parastomal hernial sac, there also was an almost rounded cystic lesion. Absence of the gallbladder at its typical position and no record of cholecystectomy raised suspicion for gallbladder projection inside the sac. Our suspicion was confirmed during the surgery. Nonexisting acute cholecystitis allowed easy reduction of the gallbladder along with the small bowel loops inside the peritoneal cavity, without proceeding to cholecystectomy at the same time. Finally, ileostomy was annulated and an end colostomy was established. Four days after the surgery, the patient was discharged from the hospital and was happy to live an almost normal life thereafter.